Tuhan, Manusia, dan Alam: Analisis Kitab Primbon Atassadhur Adammakna - Samidi, Samidi (SHAHIH : Journal of Islamicate Multidisciplinary, 2016)
AbstractThis article is the result of the library research on the divining manual book, usually known as Kitab Primbon Atassadhur Adammakna written by Pangeran Tjakraningrat. Kitab Primbon commonly consists of mystical lessons, magical practices, and oracles or fortune-telling. However, Kitab Primbon Atassadhur Adammakna precisely explains the Javanese philosophy which adopts the Islamic lessons, especially tasawuf. The lessons of God, human, and universe are appropriately described with the Javanese tradition and culture. Keeping the harmony of the relationship between human and universe is an obligation, since it also means keeping the harmony with the God, as the Creator of the universe. Keywords : God, Human, Universe, and Kitab Primbon AbstrakTulisan ini merupakan hasil kajian pustaka (library research) terhadap Kitab Primbon Atassadhur Adammakna karya Pangeran Tjakraningrat. Kitab primbon pada umumnya mengandung ajaran mistik, klenik, dan ramalan atau nujum. Namun kitab Primbon Atassadhur Adammakna ini justru menguraikan ajaran filsafat Jawa yang mengadopsi ajaran Islam, khususnya tasawuf. Konsep manusia, Tuhan, dan alam Ajaran tentang Tuhan, manusia, dan alam dijabarkan sesuai dengan adat dan budaya Jawa. Menjaga keselarasan hubungan antara manusia dengan alam adalah kewajiban, karena sama artinya menjaga keharmonisan dengan Tuhan, sebagai Sang Pencipta Semesta.Kata kunci: Tuhan, Manusia, Alam, Kitab Primbon